MUSHAF KUNO LOMBOK: Telaah Aspek Penulisan dan Teksnya - Mustopa, Mustopa (SUHUF, 2017)
This writing explains the ancient QurÃ¢â‚¬â„¢anic manuscripts of Lombok's collection of West Nusa Tenggara State Museum, Mataram, both its codicological and textual features containing a number of things such as rasm and qirÃ„ÂÃ¢â‚¬â„¢at being used, as well as tajwÃ„Â«d signs (rule of reciting the holy QurÃ¢â‚¬â„¢an) and waqf signs (mark of stopping in reciting the holy QurÃ¢â‚¬â„¢an). The study of writing style shows that the ancient manuscripts of this museum collection were influenced by the Javanese QurÃ¢â‚¬â„¢an tradition. The simple and ill-mannered writing shows that the author is an ordinary person, a kiai (Islamic local religious leader), a santri (a pious Islamic pupil), or a general public, and not a professional clerk. This study uses descriptive-analytical and comparative methods, thus it can obtain a relatively objective picture of the style and typology of writing, the use of punctuation, tajwÃ„Â«d, and waqf in each of the ancient manuscripts studied. In this study, a mapping of the motives and interests of a person in copying ancient manuscripts is also conducted.